Selected Essays on Corporate Reputation and Social Media: Collection of Empirical Evidence - Kick, Markus (Springer, 2015)
​In four empirical studies, this cumulative work provides valuable insights for marketing executives of statutory health insurance funds and social media responsible. Paper I and II provide evidence about the importance and interplay of price and corporate reputation on the market of statutory health insurance. The second part changes perspective to corporate communication issues in the social media environment. By introducing the “social media brand value chain” paper III conducts a literature review of state of the art social media research. By means of a field experiment on Facebook, paper IV shows that brands do not necessarily have to communicate via their brand fan pages in a highly interactive and vivid way to positively influence attitudinal measures among their fan base.